Zwischen Authentizität und Fiktion Die private Korrespondenz spanischer Emigranten aus Amerika, 1492-1824 - Stangl, Werner (2012)
The main focus of this study is a methodological analysis of private letters written by Spanish emigrants from the Americas to their relatives and friends back in Europe, with an intensive discussion about the interaction and blurring between the public and the private spheres in private correspondences, kept and preserved in a public space (the archive). Questions of source criticism and a detailed assessment of the scientific production on the topics of letter writing and private correspondences in general, and emigrant-letters, specially, constitute the first part of the study. Emigrant letters from the colonial period can be found in a wide array of archival sources. Private archives of noble families, merchant houses and merchant institutions often hold large vaults of correspondence of some prominent member, but also public archives in Spain provides several types of documents containing private letters: notarial records and files from court cases do contain a good number of letters. A very important source for Spanish emigrant letters, because they were written by the greatest number of different letter writers, stem from solicitations for emigration licences, which were required by Spanish subjects in order to legally cross the Atlantic Ocean. Depending on the varying contexts of their archiving, the analysis of the letters' contents requires different methods and peculiar precautions and aspects have to be reflected to reach an acceptable degree of hermeneutical understanding of each single text. The private and intimate, innate to the form of private or familiar letters as a genre, stand in a fascinating contrast to the manifold public contexts present from the production of the letter itself, to the transport, reshipment, lecture, all the way to its archiving (and lecture by the modern scholar). The central corpus of analysis are the mentioned letters from emigration solicitudes, commonly called cartas de llamada or recruitment letters. With their help, hopeful solicitors tried to prove that their husbands wanted them in order to reunite in their new home, or that a relative (quite often an uncle or cousin) wanted them to come and had work to offer. Letters of this type were also the basis of the most important existing edition of emigrant letters by Enrique Otte from 1988, a work which is generally considered the spark that triggered interest in such letters as historical sources within the historiography of Spanish America. His work, which was limited to the years 1540-1614, was followed by several other editions of emigrant letters, some of them also using cartas de llamada. However, none of these editions offered a systematical comparison of the existing editions or tried to exhaustively identify the archival series containing such letters. Most editions also made very limited use of the documents surrounding the letters in the solicitudes. Last - but not least - one has to state a complete chaos concerning the practice and standards for the edition of the original documents, which differ considerably - methodologically and qualitatively. This study, thus, also makes an effort to develop a solid basis for possible future editions. Searching in the Archivo General de Indias in Seville, 1213 hitherto unknown and unpublished letters could be added to the 1017 cartas de llamada already published in other editions. This study analysis this closed corpus quantitatively in demographic and temporal-spatial aspects and qualitatively tries to answer question about the use of the letters in the keeping-up of familiar ties and organization of chain-emigration. Special attention is also given to the communicative behaviour of the emigrants, which is studied both qualitatively - by taking a look at the strategies employed to secure the transoceanic contact despite the many obstacles like wars, shipwrecking, and lack of infrastructure - and quantitatively - by comparing the time needed for full circuits of correspondence, freq